Knowledge and attitude towards geriatric health and the associated factors among medical students of International Islamic University Malaysia - Shalihin, Mohd Shaiful Ehsan; Abd Mutalib, Nuria Syafira; Azmi, Nur Syahirah; Mohd Zin, Zahra Najwa (Malaysian Public Health Physicians’ Association, 2021)
Comprehensive care towards geriatric health can be sustained by having good knowledge and attitude among the providers. Hence, this research aims to measure the knowledge and attitude of the final year medical students towards geriatric health and determine the associated factors. A cross-sectional study was conducted among the students using structured questionnaires of Geriatric-Attitude-Scale and Palmore-Facts-on-Aging-Quiz was used. Data was analysed using Mann Whitney U test, Chi square test and Spearman correlation coefficient analysis for the association between the score and studied variables. Median score of students’ knowledges is at 14.00 (IQR 13.00) and mean score for attitude is 48.52 (+5.53) respectively. Place of residence (P= 0.01) and presence of grandparents (P= 0.04) were the significant factors that affected knowledge of students towards geriatrics while number of siblings (P= 0.05) influenced attitudes of students towards geriatrics. Improvement of current geriatric curriculum should be done with more refined implementation of gerontology course in the basic medical learning